Fiji National Roundtable Workshop June 2017: Outcomes Report - Francis, Judith Ann; Dietershagen, Jana; Jejov, Emil (Technical Centre for Agricultural and Rural Cooperation, 2017)
The CTA/IFAD/PIPSO Promoting Nutritious Food Systems in the Pacific Islands – Fiji National Roundtable Workshop took place on 28 and 29 June 2017 at the Tanoa Plaza Hotel in Suva, Fiji. Sixty-three participants representing government ministries, private sector, civil society, academia and regional/development organisations attended the two-day workshop.